2010
DOI: 10.1042/bj20101122
|View full text |Cite
|
Sign up to set email alerts
|

Three factors that modulate the activity of class D β-lactamases and interfere with the post-translational carboxylation of Lys70

Abstract: The activity of class D β-lactamases is dependent on Lys70 carboxylation in the active site. Structural, kinetic and affinity studies show that this post-translational modification can be affected by the presence of a poor substrate such as moxalactam but also by the V117T substitution. Val117 is a strictly conserved hydrophobic residue located in the active site. In addition, inhibition of class D β-lactamases by chloride ions is due to a competition between the side chain carboxylate of the modified Lys70 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 47 publications
3
78
0
Order By: Relevance
“…The kinetics of nitrocefin hydrolysis was not affected by bicarbonate concentration, as assessed by using UVspectrophotometer. Similar observations were made by Vercheval et al (26). Nitrocefin is intrinsically a chemically reactive molecule and as such partial loss or gaining of carbamylated species may not have an impact in the turnover rate of nitrocefin.…”
Section: Effect Of Co 2 On the Kinetics Of Oxa-58supporting
confidence: 87%
See 3 more Smart Citations
“…The kinetics of nitrocefin hydrolysis was not affected by bicarbonate concentration, as assessed by using UVspectrophotometer. Similar observations were made by Vercheval et al (26). Nitrocefin is intrinsically a chemically reactive molecule and as such partial loss or gaining of carbamylated species may not have an impact in the turnover rate of nitrocefin.…”
Section: Effect Of Co 2 On the Kinetics Of Oxa-58supporting
confidence: 87%
“…Hydrolysis progress curves for several ␤-lactams with OXA-10 displayed biphasic kinetics, which simplified to monophasic when buffers were supplemented with NaHCO 3 (the source of CO 2 ). These studies demonstrated that the biphasicity in kinetics was due to the decarbamylation of the lysine active site residue during the kinetics (26,27).…”
Section: Effect Of Co 2 On the Kinetics Of Oxa-58mentioning
confidence: 91%
See 2 more Smart Citations
“…The moxalactam is an extended-spectrum cephamycin that possesses a methoxy group at position 7 in the ␤-lactam ring. Previous studies suggested that this compound was poorly inactivated by class A, C, and D carbapenemases (14,16,17,24), whereas it was well hydrolyzed by class B enzymes (21). To confirm this statement, we determined the MIC values of several extended-spectrum ␤-lactams, including moxalactam, for Escherichia coli DH10B (bla KPC-3 ), E. coli DH10B (bla NDM-1 ), E. coli DH10B (bla VIM-4 ), E. coli TOP10 (pCMY-2), and E. coli J53-2 (bla OXA-48 ) recombinant or transconjugant strains, which produced KPC-3, NDM-1, VIM-4, CMY-2, and OXA-48 enzymes, respectively (7,8,12,14).…”
mentioning
confidence: 96%